2019
DOI: 10.1001/jama.2018.18085
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Survival Comparing Web-Based Symptom Monitoring vs Routine Surveillance Following Treatment for Lung Cancer

Abstract: Symptom monitoring during chemotherapy via web-based patient-reported outcomes (PROs) was previously demonstrated to lengthen survival in a single-center study. 1 A multicenter randomized clinical trial compared web-based monitoring vs standard scheduled imaging to detect symptomatic recurrence in patients with lung cancer following initial treatment. A planned interim analysis (9-month follow-up) found a significant survival benefit (19-month survival in the PRO group vs 12 months in the control group). 2 We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
390
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 399 publications
(404 citation statements)
references
References 4 publications
8
390
0
6
Order By: Relevance
“…Research is needed to test how technology can be used to improve cancer care delivery throughout the cancer care continuum from initial patient assessment to self‐care management and triage to support services. Recently, Basch et al and Denis et al found that a reporting system for patient‐reported symptoms also improved survival . Such a system could be leveraged to also provide triage to cancer rehabilitation services; including this in a rapid learning environment in which the model of care could be monitored and improved upon by stakeholders would be ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Research is needed to test how technology can be used to improve cancer care delivery throughout the cancer care continuum from initial patient assessment to self‐care management and triage to support services. Recently, Basch et al and Denis et al found that a reporting system for patient‐reported symptoms also improved survival . Such a system could be leveraged to also provide triage to cancer rehabilitation services; including this in a rapid learning environment in which the model of care could be monitored and improved upon by stakeholders would be ideal.…”
Section: Introductionmentioning
confidence: 99%
“…It has even been suggested that patients lacking computer experience may have less developed health communication skills and may thereby benefit more from a structured program for reporting symptoms . Two promising randomized trials have demonstrated lengthened patient survival when symptoms are monitored via home‐based ePROs . The first trial randomized 766 advanced cancer patients at one academic medical center during chemotherapy, while the other included 121 advanced non‐progressive lung cancer patients right after treatment, and followed them for 2 years .…”
mentioning
confidence: 99%
“…In both studies, ePRO group participants completed weekly, web‐based self‐reports of a limited number of common symptoms, while the control group received standard care. When the ePRO group participants reported a severe or worsening symptom, an email alert was triggered to the clinical staff responsible for the care of that patient, and action was taken at the clinicians’ discretion and 7.6 months longer for lung cancer patients in the ePRO group compared to the control group after 2 years .…”
mentioning
confidence: 99%
See 2 more Smart Citations